Agency Theory and the Market Timing Theory: Distinction and Resemblance - Hamad, Samer (European Scientific Journal, ESJ, 2025)
This study examines the preference for debt over equity issuance among companies, finding both positive and negative implications, and examining the financial and structural implications of financing decisions. Equity is defined as the company’s book value or the amount owed to owners upon asset liquidation, while debt refers to funds borrowed from external parties, which can be short-term (operational expenses) or long-term (growth investments). Results show that companies tend to issue debt as it reduces tax liabilities and increases post-tax cash flow available for dividends. However, a negative relationship is observed between liquidity, measured by the current ratio (CR), and the debt ratio, suggesting that higher liquidity levels lead companies to limited debt, possibly to manage agency costs arising from conflicts between creditors and owners, and between management and owners. Additionally, the negative relationship between company size and debt ratio indicates that larger companies, with higher profitability, tend to maintain lower debt levels. The findings also emphasize the importance of aligning management incentives with shareholder interests through compensation tied to profitability and stock price performance. Nonetheless, agency costs associated with debt management persist. This approach ensures that management is incentivized to act in the owners’ best interest while minimizing agency costs. These findings highlight the complex dynamics of capital structure decisions and suggest that management strategies should focus on optimizing liquidity levels and aligning incentives to balance growth opportunities with shareholder value maximization. The study provides a comprehensive evaluation of how equity and debt financing preferences impact corporate financial strategies and behaviors.